x 4 − 2 x 3 + x = 2 ( x 2 − x )
Find the sum of all real x that satisfy the above equation.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Did the same way :)
lol, I just guessed x = − 1 , 0 , 1 , 2 :D @Jerry Han Jia Tao
Log in to reply
LIKE A GOD :D
Yes, there are four real roots -1, 0, 1, and 2.
Nice solution
Log in to reply
Great problem as well, post more of such problems in the future!
Yeah, your problems are awesome even though i could barely solve any.
Has four root 0 1 -1 2
Log in to reply
Hope my edited solution has made it clearer.
x 4 − 2 x 3 + x x 4 − x 3 − x 3 + x 2 − x 2 + x x 2 ( x 2 − x ) − x ( x 2 − x ) − ( x 2 − x ) ( x 2 − x ) 2 − ( x 2 − x ) y 4 − y 2 y 4 − y 2 − 2 y y ( y 3 − y − 2 ) y ( y − 2 ) ( y 2 + 2 y + 1 ) = 2 ( x 2 − x ) = 2 ( x 2 − x ) = 2 ( x 2 − x ) = 2 ( x 2 − x ) Let y 2 = x 2 − x = 2 y = 0 = 0 We note that y = 2 is a root. = 0 We note that y 2 + 2 y + 1 = 0 has no real root.
⟹ ⎩ ⎪ ⎪ ⎪ ⎪ ⎨ ⎪ ⎪ ⎪ ⎪ ⎧ y = 0 y = 2 ⟹ x 2 − x = 0 ⟹ x 2 − x = 2 ⟹ { 0 1 ⟹ { − 1 2
Therefore, the sum of roots is 0 + 1 − 1 + 2 = 2 .
Nice solution sir, did the same! (+1)!
Yes,Viet Nam
x 4 − 2 x 3 + x = 2 ( x 2 − x )
On squaring:
x 8 + 4 x 6 + x 2 − 4 x 7 − 4 x 4 + 2 x 5 = 2 x 2 − 2 x
x 8 − 4 x 7 + 4 x 6 + 2 x 5 − 4 x 4 + x 2 − 2 x 2 + 2 x = 0
x 8 − 4 x 7 + 4 x 6 + 2 x 5 − 4 x 4 − x 2 + 2 x = 0
On factorizing:
x ( x + 1 ) ( x − 1 ) ( x − 2 ) ( x 4 − 2 x 3 + x 2 + 1 ) = 0
Solutions:
x 1 = 0
x 2 = − 1
x 3 = 1
x 4 = 2
x 5 = − 0 . 3 0 0 2 4 3 − 0 . 6 2 4 8 1 1 i
Sum of real solutions = 0 − 1 + 1 + 2 = 2
Try Polynomial Equation Solver on Bing!!!
Hi brooh... I just use vieta theorems... is can?
Problem Loading...
Note Loading...
Set Loading...
Let a = x 2 − x x 4 − 2 x 3 + x = a 2 − x 2 + x = a 2 − a a 2 − a = 2 a a 4 − 2 a 3 + a 2 = 2 a a 4 − 2 a 3 + a 2 − 2 a = 0 a ( a − 2 ) ( a 2 + 1 ) = 0 a = 0 , 2 x 2 − x − 2 = 0 or x 2 − 2 x = 0 x = 0 , − 1 , 1 , 2 Therefore, the answer is 2